Giant multilocular prostatic cystadenoma in a young man: A case report from Jordan - Mohammad Kh. Alzawahreh; Ala'a B. Al‐Tammemi; Mustafa I. Al‐Shalah; Ahmad Abuebeid; Zaid Manaserh; Baha'a Alhroub; Moath O. Badawi; Anas M. Abu‐Zanouneh; Maen Malkawi (Clinical Case Reports, 2022)
Abstract Giant Multilocular Prostatic Cystadenoma (GMPC) is one of the rare benign tumors of the prostate. This report presents a case of a young man who has been recently diagnosed with GMPC. Our report highlights the importance of timely diagnosis and treatment, considering the overlapping symptoms with other common urinary conditions.